2019
DOI: 10.1007/s10522-019-09835-0
|View full text |Cite|
|
Sign up to set email alerts
|

Development, lifespan and reproduction of spider mites exposed to predator-induced stress across generations

Abstract: Predator-induced stress shows pronounced effects on prey by inducing behavioural, morphological, and physiological responses. Increasing evidence shows that these antipredator responses may also lead to changes in life-history traits such as aging and lifespan. However, little is known about how predator cues influence the fitness of preys and their transgenerational effects. Parental spider mites (Tetranychus urticae) were either raised on a leaf disc with or without cues from a natural predator (Phytoseiulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 43 publications
13
50
0
Order By: Relevance
“…Most traits (e.g., weight, body size, survival, cautiousness) did not show any sex-specific pattern: daughters and sons were equally affected by the parental environment (Coslovsky and Richner, 2011;Stein and Bell, 2014;Basso and Richner, 2015a,b;Hellmann et al, 2019) (pattern c in Figure 4). For the other traits, parental exposure influenced only one sex and not the other (patterns a and b in Figure 4: Coslovsky and Richner, 2011;Basso and Richner, 2015a;Hellmann et al, 2019;Li and Zhang, 2019). For instance, paternal exposure to predator-cues increased activity of sons but not daughters-this could be adaptive, as only males may benefit from higher activity under predation risk in sticklebacks.…”
Section: Offspring Sex-specific Transgenerational Plasticitymentioning
confidence: 99%
See 3 more Smart Citations
“…Most traits (e.g., weight, body size, survival, cautiousness) did not show any sex-specific pattern: daughters and sons were equally affected by the parental environment (Coslovsky and Richner, 2011;Stein and Bell, 2014;Basso and Richner, 2015a,b;Hellmann et al, 2019) (pattern c in Figure 4). For the other traits, parental exposure influenced only one sex and not the other (patterns a and b in Figure 4: Coslovsky and Richner, 2011;Basso and Richner, 2015a;Hellmann et al, 2019;Li and Zhang, 2019). For instance, paternal exposure to predator-cues increased activity of sons but not daughters-this could be adaptive, as only males may benefit from higher activity under predation risk in sticklebacks.…”
Section: Offspring Sex-specific Transgenerational Plasticitymentioning
confidence: 99%
“…No studies examined TGP expression only in the embryonic stage. To our knowledge, 14 studies (25%) explored TGP expression in response to predation risk at different times in offspring life, either within an offspring stage or among different stages (Tollrian, 1995;Agrawal et al, 1999;Sheriff et al, 2010;Richner, 2011, 2012;Giesing et al, 2011;Basso et al, 2014;Bestion et al, 2014;Stratmann and Taborsky, 2014;Basso and Richner, 2015a,b;St-Cyr and McGowan, 2015;Freinschlag and Schausberger, 2016;Li and Zhang, 2019). Screening these studies, different scenarios are observed (Figure 2).…”
Section: Expression Time Of Transgenerational Plasticity: Offspring Smentioning
confidence: 99%
See 2 more Smart Citations
“…Predator-induced stress (predation risk or the fear of becoming prey) has been shown to have pronounced effects on prey species by inducing behavioral, morphological, and physiological responses (30)(31)(32)(33). In two species of water fleas (Daphnia longispina and Diaphanosoma brachyurum) (34) and in parental spider mites (Tetranychus urticae) (35), it was recently shown that the physiological response to predator-induced stress mediated by predator cues caused pronounced effects on the aging pattern. Our life-history model does not incorporate such effects, as it implies that the rate of somatic damage accumulation may be under deliberate regulatory control driven by perceptual information and anticipatory inference (36).…”
Section: Discussionmentioning
confidence: 99%